Exophytic Parietal Skin Metastases of Renal Cell Carcinoma - Karim Kassam; Elizabeth Tiong; Ezra Nigar; Mahesh Kumar (Case Reports in Dermatological Medicine)
The common sites for metastasis of renal cell carcinoma are lung, kidney, adrenal glands, liver, and contralateral kidney. We report an unusual case of cutaneous metastasis of renal cell carcinoma in a 68-year-old woman who was treated for renal cell carcinoma with partial right nephrectomy and multikinase angiogenesis inhibitor (sunitinib) 10 years ago.